LncRNA DANCR contributes to tumor progression via targetting miR-216a-5p in breast cancer: lncRNA DANCR contributes to tumor progression. Issue 4 (23rd April 2019) - Tao, Weiyang; Wang, Chunyang; Zhu, Bifa; Zhang, Guoqiang; Pang, Da
Abstract : Breast cancer, the most frequently occurring malignant tumor, has high mortality rate, especially triple-negative breast cancer (TNBC). LncRNA-differentiation antagonizing non-protein coding RNA (lncRNA DANCR) has been found that its aberrant expression was associated with tumor progression and it was promising to be a potential target for cancer therapy. The goal of the present study was to explore the biological effects and underlying mechanism of DANCR in breast cancer. Our results showed that DANCR was up-regulated in TNBC tissues and breast cancer cells compared with normal breast tissues and cells, and higher DANCR level suggested poorer prognosis, implying that it was promising to be a novel biomarker used for TNBC diagnosis and prognosis. To better research the functions and mechanism of DANCR on breast cancer cells, we selected two cell lines used for next study: one TNBC cell line–MDA-MB-231 and one ER-positive breast cancer cell line–MCF-7. Further study indicated that DANCR overexpression significantly promoted cell proliferation and invasion in vitro and contributed to tumor growth in vivo . To deeply understand its molecular mechanism, miRNA-216a-5p was identified as a target of DANCR by bioinformatic analysis. Experiments demonstrated that miRNA-216a-5p interacted with DANCR and its inhibitor could weaken the influences induced by DANCR knockdown for cancer cells, including cell proliferation and invasion, and the expression of Nanog, SOX2, and OCT4. Therefore, DANCR might act as a tumor promoter by targetting miRNA-216a-5p, which might provide a potential therapy target for breast cancer treatment.